2011
DOI: 10.1002/bdm.759
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Linear Perception of Nonlinearity: Use of a Physical Representation

Abstract: Research shows that while judging accumulations of quantities over time (e.g., money in a bank account or CO 2 in Earth's atmosphere), people assume that the shape of the accumulation is similar to the shape of the inflow (i.e., people rely on a correlation heuristic). Relying on the correlation heuristic is particularly worrisome for Earth's climate, as judging the CO 2 accumulation according to its emissions (inflow) would underestimate the actual (nonlinear) increase. This misperception undermines the serio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In the main SF task, the answer alternative that was selected by most participants (about 45%) was the pattern matching alternative, and pattern reasoning was the most frequently used explanation for choosing this alternative. This finding is in line with previous research, demonstrating a strong tendency for pattern matching (e.g., Dutt and Gonzalez 2013;Reichert et al 2015;Cronin et al 2009;Sterman 2008).…”
Section: Ways Of Reasoning Provide Additional Theoretical Insights Insupporting
confidence: 93%
“…In the main SF task, the answer alternative that was selected by most participants (about 45%) was the pattern matching alternative, and pattern reasoning was the most frequently used explanation for choosing this alternative. This finding is in line with previous research, demonstrating a strong tendency for pattern matching (e.g., Dutt and Gonzalez 2013;Reichert et al 2015;Cronin et al 2009;Sterman 2008).…”
Section: Ways Of Reasoning Provide Additional Theoretical Insights Insupporting
confidence: 93%
“…This average speed fallacy, along with both the AFEF and the MPG illusion, relates to a basic tendency to treat nonlinear relationships as linear. Various studies have shown this "illusion of linearity" to exist in a range of situations demanding relational estimates, including population growth, the heating and cooling of objects, and others (Confrey & Smith, 1995;De Bock, Van Dooren, Janssens, & Verschaffel, 2002;De Bock, Verschaffel, & Janssens, 1998;Dutt & Gonzalez, 2013;Freudenthal, 1983;Van Dooren, De Bock, Depaepe, Janssens, & Verschaffel, 2003;Van Dooren, De Bock, Hessels, Janssens, & Verschaffel, 2004). As Freudenthal has noted, "Linearity is such a suggestive property of relations that one readily yields to the seduction to deal with each numerical relation as though it were linear" (Freudenthal, 1983, p. 267).…”
Section: Consequences Of the Afefmentioning
confidence: 99%
“…This misconception assumes that stabilizing emissions would rapidly stabilize the concentration; and, emission cuts would quickly reduce the concentration and damages from climate change. This reasoning is incorrect because reliance on the correlation heuristic significantly underestimates the time delays existent between reductions in CO 2 emissions and their effect on the CO 2 concentration ( Sterman, 2008 ; Dutt and Gonzalez, 2012a , 2013a , b ; Kumar and Dutt, unpublished).…”
Section: Introductionmentioning
confidence: 99%